Research Status of Wear Prediction of Spherical Friction Pair - Jiang, Peiji (International Journal of Mechanical and Electrical Engineering, 2024)
Spherical friction pairs are widely used in mechanical equipment, and predicting the wear of spherical friction pairs can help evaluate and predict bearing life. At present, when using the finite element analysis method to calculate the wear of spherical friction pairs, it is still necessary to simulate under idealized conditions, and the limitations of calculation amount and time need to be considered. The accuracy of the prediction method is measured by experimental means to measure the wear amount, which can be characterized by measuring the mass, volume, or wear thickness of the material under grinding. Based on the wear test methods used and the characteristics of the tested materials, suitable wear characterization parameters and measurement methods can be selected. This article also analyzes the influence of friction pair materials and service conditions on the wear of spherical friction pairs. Finally, the article looks forward to the development trend of predicting the wear of spherical friction pairs.